Nano-bioceramics production from razor shell - (:unkn) unknown (Trans Tech Publications Ltd, 2012)
The regeneration potential of human bone is limited in the cases of repairing large bone defects, such as those associated with comminuted fractures or bone tumor resection. In most cases, autogenous and allogenic bones are used as bone grafts. However, the amount of both of them is severely limited. Nowadays, natural biomaterials are in question, like corals, cuttlefish, and various nacre species, or hydroxyapatite (HA) made from egg shells. The present work aims at preparing inexpensive nano-sized HA and whitlockite particles from various raw materials of natural-biological origin. Razor shells (ensis ensis) were collected from beaches of Thessaloniki in Greece. Each sample was reduced to particle size <100 μm and DTA/TG was employed to determine their exact CaCO3 content. The suspended raw powders were put on a hotplate. The temperature was set to 80°C for 15 min. Then, equivalent amount of H 3PO4 was added, drop by drop, into the solution. Different Ca/P ratios were tried. The reaction was ultrasonically assisted and continued for 8h. Then, to evaporate the liquid part, the mixture was put into an incubator at 100°C for 24 h and the resulting dried sediment was collected. The morphology of the produced powders was examined by SEM and revealed nano-sized particles. X-ray diffraction analysis indicated various Ca-phosphate phases, i.e. monetite and calcium phosphate hydrate. Thus, razor shells could be an alternative source for calcium phosphate ceramics production. In this study, long nacre shells were converted to various bioceramic structures with simple ultrasonic method without using hydrothermal method, which is carried out in a close vessel heated in a furnace and could cause accident if the vessel is worn. Chemical ultrasonic method is very safe and reliable method for bioceramic production from aragonite structures. © (2012) Trans Tech Publications.
Keywords: Characterization; Monetite; Natural bioceramics; Razor shell; Ultrasound